Rethinking democratic equality: isonomy, isogoria, isotimia (Colección, 2017)
The democratic promise today is unfulfilled. A growing crisis in representative legitimacy put into question the way democratic politics are being done. In this sense, this article tries to delve into the centerpiece of the democratic dream: the political equality that enters the world by the power of the demos. In this line, we offer an invitation to rethink the democratic equality by taking into consideration the founding principles of Athenian democracy (Isonomy, Isogoria Isotimia) weighing them against the modern democratic principles (Rule of law, representative principle, method of election). This way, determining in what way does modern representative democracy truly commits to the principle of political equality. And through this, discover, somehow, the causes and reasons of the legitimacy crisis that besets us.
Keywords: Democracy; Representation; Equality; Isonomy; Isogoria; Isotimia